Refining the psychiatric syndrome of anti‐N‐methyl‐d‐aspartate receptor encephalitis. (10th July 2018) - Warren, N.; Siskind, D.; O'Gorman, C.
Abstract : Objective: To review the psychiatric symptoms of anti‐ N ‐methyl‐d ‐aspartate (NMDA) receptor encephalitis, in an attempt to differentiate the presentation from a primary psychiatric disorder. Method: A systematic literature review of PubMed and EMBASE of all published cases of anti‐NMDA receptor encephalitis was performed from inception to January 2018. Results: There were 706 cases of anti‐NMDA receptor encephalitis identified. Cases were typically young (mean age 22.6 years, SD 14.8), female (F : M ratio 3.5 : 1) and presented with significant behavioural disturbance. Reported behaviour was most commonly severe agitation and aggression, abnormal speech, and catatonia. Psychosis occurred in 45.8% of cases. Investigation results were inconsistent (MRI abnormal in 35.6%, EEG abnormal in 83.0%) and non‐specific. Psychiatric treatment often required multiple psychotropics, and there may be increased risk of significant side‐effects such as neuroleptic malignant syndrome. Prognosis was usually good; however, cognitive and behavioral symptoms remained prominent during recovery, and psychiatrist involvement was required in this period. Conclusion: The presentation of anti‐NMDA receptor encephalitis is variable. However, there are often psychiatric features which are atypical to a primary psychiatric illness, such as severe agitation, speech abnormalities, and catatonia, which may help early identification.